Validation and psychometric properties of the portuguese version of the Coronavirus Anxiety Scale (CAS) and fear of COVID-19 Scale (FCV-19S) and associations with travel, tourism and hospitality - Magano, José (2021)
The aim of this study is to determine the anxiety and fear related to coronavirus disease 2019 (COVID-19) and their associations with travel, tourism and hospitality, in the Portuguese population. The Coronavirus Anxiety Scale (CAS) and Fear of COVID-19 Scale (FCV-19S) were validated for the Portuguese population and correlations with issues related to travel, tourism and hospitality were established. CAS and FCV-19S presented a good adjustment model and solid reliability and validity. Correlations between CAS and FCV-19S and the perception of the impact of COVID-19 in travel, tourism and hospitality were found. Participants considered that COVID-19 mainly affected their holidays and leisure time. However, the strongest correlation established was between total FCV-19S and emotional fear FCV-19S and the fear of attending hotel facilities. The Portuguese versions of CAS and FCV-19S are reliable psychological tools to assess anxiety and fear in relation to COVID-19 for the general population. The use of hotel facilities is the most threatening issue related to travel, tourism and hospitality. The results suggest that hotels should invest in hygiene and safety measures that allow users to regain confidence in hotel equipment.